Self- Management practice Gaps among Patients with Hypertension in KSA: Narrative Review - Areej M. Alhaddad; Samah M. Sofar; Aisha Alhofaian (Evidence-Based Nursing Research)
Context: Hypertension (HTN) is identified as the most common non-communicable disease. HTN is considered one of the causes of premature mortality worldwide.